2014
DOI: 10.1105/tpc.114.128512
|View full text |Cite
|
Sign up to set email alerts
|

eQTL Mapping of Transposon Silencing Reveals a Position-Dependent Stable Escape from Epigenetic Silencing and Transposition of AtMu1 in the Arabidopsis Lineage

Abstract: Transposons are massively abundant in all eukaryotic genomes and are suppressed by epigenetic silencing. Transposon activity contributes to the evolution of species; however, it is unclear how much transposition-induced variation exists at a smaller scale and how transposons are targeted for silencing. Here, we exploited differential silencing of the AtMu1c transposon in the Arabidopsis thaliana accessions Columbia (Col) and Landsberg erecta (Ler). The difference persisted in hybrids and recombinant inbred lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…If a TE inserts into an exon or otherwise disrupts the gene's activity, this allele may be selected against, and this may result in the allele's disappearance from the population. Alternatively, a TE may escape silencing altogether by inserting into the 39 untranslated region of an essential gene (Kabelitz et al, 2014), which could provide a safe-haven location that the cell cannot afford to silence. Ultimately, the majority of intragenic TEs do not remain complete or active, as the selection for proper gene activity leads to TE silencing (discussed further below) and/or TE sequence deletion.…”
Section: Tes Within Genesmentioning
confidence: 99%
“…If a TE inserts into an exon or otherwise disrupts the gene's activity, this allele may be selected against, and this may result in the allele's disappearance from the population. Alternatively, a TE may escape silencing altogether by inserting into the 39 untranslated region of an essential gene (Kabelitz et al, 2014), which could provide a safe-haven location that the cell cannot afford to silence. Ultimately, the majority of intragenic TEs do not remain complete or active, as the selection for proper gene activity leads to TE silencing (discussed further below) and/or TE sequence deletion.…”
Section: Tes Within Genesmentioning
confidence: 99%
“…The degree of reactivation correlated with the magnitude of JMJ24 overexpression. The analysis of unspliced AtMu1c transcripts (Kabelitz et al, 2014) in jmj24-2 and 35S::JMJ24 plants (Supplemental Fig. S2) suggests that the release of silencing occurs at the level of transcription (i.e.…”
Section: Jmj24 Counteracts Transcriptional Silencing Of Atmu1cmentioning
confidence: 99%
“…For AtMu1, it was shown that it is targeted by several epigenetic silencing pathways, including RdDM (Lippman et al, 2003;Bäurle et al, 2007), and AtMu1 transposition was found in DNA methylation-deficient backgrounds and in the vegetative nucleus of pollen, where global reactivation of TEs occurs (Singer et al, 2001;Slotkin et al, 2009). AtMu1c is the most active of the three AtMu1 copies (Kabelitz et al, 2014). At the phylogenetic level, AtMu1c transposition was found in the Arabidopsis lineage (Kabelitz et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This in general suggested that specific genomic locations and chromatin environments may favor escape of TEs from epigenetic silencing. 24 Within the nucleus, silent heterochromatin regions are visible as densely stained chromocenters that in Arabidopsis mainly comprise centromeric and pericentromeric heterochromatin. Chromocenters de-condense during imbibition and seed germination and progressively reform during the first days of post-germination seedling growth, following extensive chromatin rearrangements.…”
Section: Organized Genome In An Organized Nucleusmentioning
confidence: 99%